Encyrtidae (Hymenoptera: Chalcidoidea) from China, with the description of two new species - Wang, Haiyang; Zhang, Chenghui; Xue, Hao; Xi, Chunxiang; Yang, Zening; Zu, Guohao (Zootaxa, 2023)
Following a survey of parasitoid wasps, the number of encyrtid species known from China has increased from 594 to 601. Five new species records are noted, and two new species, Aphycus nigriceps Zu & Wang, sp. nov. and Psyllaephagus chinensis Zu & Wang, sp. nov., are described. Data of all species identified in our survey and a list of known species of Encyrtidae from Tianjin are provided.